2018
DOI: 10.1074/jbc.ra118.004304
|View full text |Cite
|
Sign up to set email alerts
|

Thylakoid membrane lipid sulfoquinovosyl-diacylglycerol (SQDG) is required for full functioning of photosystem II in Thermosynechococcus elongatus

Abstract: Sulfoquinovosyl-diacylglycerol (SQDG) is one of the four lipids present in the thylakoid membranes. Depletion of SQDG causes different degrees of effects on photosynthetic growth and activities in different organisms. Four SQDG molecules bind to each monomer of photosystem II (PSII), but their role in PSII function has not been characterized in detail, and no PSII structure without SQDG has been reported. We analyzed the activities of PSII from an SQDG-deficient mutant of the cyanobacterium by various spectros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 39 publications
2
20
0
Order By: Relevance
“…5). Mass spectrometric analysis showed that the observed molecular weights of the co-purified lipids are identical to the calculated values of these thylakoid membrane-specific lipids 30 , unequivocally confirming their chemical identities ( Supplementary Fig. 8c).…”
Section: Resultssupporting
confidence: 68%
See 1 more Smart Citation
“…5). Mass spectrometric analysis showed that the observed molecular weights of the co-purified lipids are identical to the calculated values of these thylakoid membrane-specific lipids 30 , unequivocally confirming their chemical identities ( Supplementary Fig. 8c).…”
Section: Resultssupporting
confidence: 68%
“…8c). Given that we purified the endogenous NDH-1LΔV complex from T. elongatus thylakoid membranes with a mild detergent (digitonin), the lipids we found in the NDH-1L structure are very likely physiologically relevant and reflect their actual binding positions in NDH-1L in vivo, suggesting that lipids in NDH-1L may play important roles as lipids found in other photosynthesis complexes of cyanobacteria 30 .…”
Section: Resultsmentioning
confidence: 92%
“…The other important difference is the lipid molecules found in the present structure and those of the previous structures. Lipids play important roles in the assembly and functions of membrane‐protein complexes (Hasan et al, 2011; Mizusawa and Wada, 2012; Kansy et al, 2014; Nakajima et al, 2018), but are difficult to identify in the X‐ray crystallography due to the weak electron density of their acyl chains. We identified five new lipids in the present structure compared with the previous 2.8 Å structure (4XK8) (Qin et al, 2015); among them, four are located in the Lhca 1‐4 dimer.…”
Section: Discussionmentioning
confidence: 99%
“…PSII is a multi-pigment transmembrane protein complex involved in converting light energy into electrochemical potential energy ( Adachi et al, 2008 ). The X-ray crystal structures of PSII from red alga Cyanidium caldarium ( Ago et al, 2016 ), cyanobacterium Thermosynechococcus elongatus ( Nakajima et al, 2018 ), and the cryo-EM structure of PSII from green alga Chlamydomonas reihardtii ( Sheng et al, 2019 ), the marine diatom Chaetoceros gracilis ( Pi et al, 2019 ), and the higher plants Arabidopsis thaliana ( van Bezouwen et al, 2017 ), Spinacia oleracea ( Wei et al, 2016 ), and Pisum sativum ( Su et al, 2017 ) have revealed the structural basis of energy transfer, electron transfer, and photoprotection within the photosystem. The main subunits of PSII include the reaction center D1, D2 protein, and chlorophyll-a binding proteins, CP43 and CP47.…”
Section: Introductionmentioning
confidence: 99%